2001
DOI: 10.1183/09031936.01.17406470
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen desaturation on the six-minute walk test and mortality in untreated primary pulmonary hypertension

Abstract: There are no reliable predictors of mortality in primary pulmonary hypertension (PPH). This study assessed whether exercise oxygen desaturation and distance achieved during a six-minute walk are associated with mortality in moderately symptomatic patients with PPH.Thirty-four patients with PPH underwent a pretreatment six-minute walk test, and an invasive haemodynamic assessment of pulmonary vasodilator reserve, to select the best treatment option (epoprostenol in 27 and nifedipine in 7). Median follow-up was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
1
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(150 citation statements)
references
References 21 publications
6
126
1
14
Order By: Relevance
“…In particular, in the short-distance group the survival rate at 20 months was 20%, compared with the long-distance group in which there was a 90% survival rate [197]. Exercise-induced hypoxaemia as measured by pulse oximetry during the 6-MWT was observed to be significantly predictive of mortality in patients with PPH [198].…”
Section: -Mwd and Arterial Desaturationmentioning
confidence: 91%
“…In particular, in the short-distance group the survival rate at 20 months was 20%, compared with the long-distance group in which there was a 90% survival rate [197]. Exercise-induced hypoxaemia as measured by pulse oximetry during the 6-MWT was observed to be significantly predictive of mortality in patients with PPH [198].…”
Section: -Mwd and Arterial Desaturationmentioning
confidence: 91%
“…Myiamoto et al 13 showed that the distance walked decreases in proportion to the increase in functional class and those who walked fewer than 332 meters had a higher mortality rate when compared to individuals who walked more than that distance 13,34 . These authors also showed that, for each 50-meter increase in the 6MWT, there was an 18% decrease in the risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…5 The 6MWT is a significant predictor of survival in patients with IPAH. [7][8][9][10][11] It is still used in clinical trials for IPAH medication use. 12 Although performing a simpler submaximal test, like the 6MWT, with children with IPAH may predict peak V o 2 , it would not give health care professionals the necessary information to evaluate functional capacity.…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition, the 6MWT is a significant predictor of survival in patients with pulmonary hypertension [7][8][9][10][11] and is used in clinical trials for IPAH medications. 12 In addition to other health limiting and debilitating conditions, patients with lung or heart disease may show a reduced 6-minute walk distance (6MWD).…”
Section: Doi: 101097/hcr0000000000000174mentioning
confidence: 99%